Synthesis and Biological Evaluation of Sugar Induced Thiazole Derivatives (The Chittagong University Journal of Science, 2021)
The starting materials, 2-amino-4-phenylthiazole and 2-amino-4,5,6,7-tetrahydrobenzo[d]thiazole, were prepared by reacting thiourea with acetophenone and cyclohexanone in the presence of iodine under heating on a water bath with occasional stirring, respectively. Reaction of 2-amino-4-phenylthiazole and 2-amino-4,5,6,7-tetrahydrobenzo[d]thiazole with various sugars afforded  corresponding N-glycoside derivatives in good yields. The structures of the synthesized N-glycosides derivatives have been established on the basis of their IR and NMR spectral data. The obtained compounds were screened for their antimicrobial activity.  Some of them were found to possess significant activities, when compared to standard drugs.The Chittagong Univ. J. Sci. 40(1) : 68-84, 2019